Insusceptibility of fetal intestinal mucosa and fetal cells to Clostridium difficile toxins - CHANG Te-wen; SULLIVAN Nadine M; WILKINS Tracy D (Acta Pharmacologica Sinica, 2016)
Infants are often carrying toxigenic Clostridium difficile in large numbers in the gastrointestinal tract without evidence of ill effects. We cultivate human amnion (epitheloid cells) and chorion (fibroblasts) in vitro and determine their susceptibility to C difficile toxin A and B three times weekly for a period of 3 weeks. On continued toxin exposure, these cells were found to be relatively insensitive to toxins during the first week of cultivation. When toxin exposure was limited to 1 h, the period of insensitivity was prolonged further. As cell cultures grew older, both types of cells gradually gained susceptibility to toxins. On subculture, neither amnion nor chorion exhibited early insensitivity to toxins, as did serially passed human lung fibroblasts (MRC-5). Fetal intestinal mucosal tissue did not absorb toxin A or B when exposed, while adult mucosal tissue did so readily. Meconium and cord serum showed no neutralizing activity. Our study suggests that resistance of infantile intestine to C difficile toxins is probably related to the nature of intestinal cells rather than intraluminal factors.